Solid state chemistry - Ropp, R. C. (Elsevier, 2003)
Solid State Chemistry is a general textbook, composed for those with little background knowledge of the subject, but who wish to learn more about the various segments of solid state theory and technology. The information is presented in a form that can easily be understood and will be useful to readers wishing to build on their own store of knowledge and experience. Well presented in easy to understand format. Informative textbook aimed primarily at the novice. Comprehensively covers the segments of solid state theory and technology.